Efficient In Vitro Expansion of Human Immunodeficiency Virus (HIV)-Specific T-Cell Responses by gag mRNA-Electroporated Dendritic Cells from Treated and Untreated HIV Type 1-Infected Individuals - Van Gulck, Ellen R. (American Society for Microbiology (ASM), 2008)
Developing an immunotherapy to keep human immunodeficiency virus type 1 (HIV-1) replication suppressed while discontinuing highly active antiretroviral therapy (HAART) is an important challenge. In the present work, we evaluated in vitro whether dendritic cells (DC) electroporated with gag mRNA can induce HIV-specific responses in T cells from chronically infected subjects. Monocyte-derived DC, from therapy-naïve and HAART-treated HIV-1-seropositive subjects, that were electroporated with consensus codon-optimized HxB2 gag mRNA efficiently expanded T cells, secreting gamma interferon (IFN-γ) and interleukin 2 (IL-2), as well as other cytokines and perforin, upon restimulation with a pool of overlapping Gag peptides. The functional expansion levels after 1 week of stimulation were comparable in T cells from HAART-treated and treatment-naïve patients and involved both CD4(+) and CD8(+) T cells, with evidence of bifunctionality in T cells. Epitope mapping of p24 showed that stimulated T cells had a broadened response toward previously nondescribed epitopes. DC, from HAART-treated subjects, that were electroporated with autologous proviral gag mRNA equally efficiently expanded HIV-specific T cells. Regulatory T cells did not prevent the induction of effector T cells in this system, whereas the blocking of PD-L1 slightly increased the induction of T-cell responses. This paper shows that DC, loaded with consensus or autologous gag mRNA, expand HIV-specific T-cell responses in vitro.